MENENTUKAN VARIABILITAS SPASIAL ALBEDOPADA WILAYAH BALI MENGGUNAKAN DATA SATELIT MODIS BRDF MCD43A1 TAHUN 2005 - 2012 - Meri Monika Sari, Ni Wayan; Sukarasa, I Ketut; Hendrawan, I Gede (BULETIN FISIKA; Vol 16 No 1 (2015): BULETIN FISIKA, 2015)
A research has been conducted to determine the variability of the albedo in Bali using MODIS BRDF MCD43A1 satellite data started from 2005 until 2012. The data used in this study is MODIS BRDF MCD43A1 data and MODIS Aerosol Optical Depth data. From MODIS BRDF MCD43A1 data, black sky and white sky albedo were calculated. The results of black sky and white sky albedo combined together and with MODISAerosol Optical Depth data to find the blue sky albedo (actual albedo), then monthly average of blue sky albedoused todetermine the spatial albedo variability in Bali. Spatial annual variability of actual albedo in Bali during 2005 – 2012 reached the highest peak in 2008 and lowest in 2010. Monthly average of actual albedo started from September-October while the lowest is in January - February.  Keywords : Albedo, MODIS BRDF MCD43A1, MODIS Aerosol Optical Depth, Black Sky albedo, White Sky Albedo, Blue Sky Albedo (Actual Albedo)